Estimativa da evapotranspiração mensal no Estado do Paraná - Abumanssur, Calil (2006)
A set of measurements of daily average temperatures of 22 agrometeorológicas stations of the Agronomic Institute of the Paraná-IAPAR in operation, were compiled originating monthly storms series matrices of temperature that permitted to calculate to evapotranspiration by the Method of Camargo from which were obtained values of the evapotranspiration month to month for each one of the distinct stations. It applied the models of the gama distribution functions, log-normal and generalized of extreme value was utilizing the results of the monthly evapotranspiration for calculate the probable value with 75% of occurrence probability. For verification of adjustment of the curves of variation of the functions distribution of the models log-normal end gamma the method of Kolmogorov-Smirnov was used, for the generalized model of extreme values the verification of the adjustment was used of the method of Wang. As they turned out was observed the monthly variation of the values of evapotranspiration to the long one of the months in the State, where the tendency of regions more to the north will have the biggest values estimated of sheet of evapotranspiration and in the stations situated in areas of bigger relative altitudes will present sheets values minors. As regards the models range, log-normal and generalized extreme value, utilized for estimate of the evapotranspiration potential, if adjusted satisfactorily. With the values of each month, considering the probability of 75% of occurrence, in each one of the stations, was mounted the map of the isolines that represent the variability of the evapotranspiration potential, according to model gama, on the cartographic base of the State of the Paraná/Brazil.